TEACHER’S WORK VALUES: A KEY TO ENHANCING WORK ENGAGEMENT: English - Aquino, Rommel; CASTILLO, SHIELA; HONRADO, MARVIN (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
The school is the cornerstone of the global education system, with educators crucial to providing high-quality education. Outstanding teacher performance leads to positive student experiences, and teacher engagement is key to stakeholder satisfaction. However, there is a gap in understanding how specific work values influence teacher engagement. This study investigates the relationship between teachers' work values and their engagement levels at the College of Business and Public Administration, Eulogio "Amang" Rodriguez Institute of Science and Technology (Manila Campus). Using purposive sampling, 69 full-time and 21 part-time faculty members participated. Key findings indicate that both full-time and part-time faculty rated their overall engagement as "Engaged," particularly in areas like work-life balance, growth opportunities, and feedback. However, a significant difference in work-life balance was observed between full-time and part-time faculty, while other areas showed no such difference. Teachers rated their work values—such as economic returns, achievement, and job security—as "Observed," with no significant variation between the two groups. A strong relationship between work values and engagement was found. This study highlights the need to align work values with professional practices to enhance teacher engagement. By fostering an environment that supports autonomy, growth, and feedback, schools can reduce absenteeism, lower turnover, and improve overall performance. Ultimately, the research provides evidence-based strategies to create a positive educational environment, enhance stakeholder satisfaction, and ensure the long-term success of educational institutions.